2020
DOI: 10.1016/j.rpor.2019.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Frameless radiosurgery for intraocular metastatic tumor: Case report

Abstract: The aim of this case report is to describe the technique and response using frameless radiosurgery technique in intraocular metastases.Background: Intraocular metastases are the most common malignant lesion within the eye and its prevalence is probably underestimated. This is of great interest for oncologist as there are new treatment options with high rates of tumor control maintaining patient's quality of life.Case Report: We report a case of a 54-year-old female with intraocular metastases from breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…There is no consensus on an optimal radiotherapy regime for choroidal metastases [8], but we prefer a shorter hypofractionated regime of 20 Gy over 5 days. It is important that the radiotherapy course not be protracted as choroidal metastases are usually part of the disseminated systemic disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no consensus on an optimal radiotherapy regime for choroidal metastases [8], but we prefer a shorter hypofractionated regime of 20 Gy over 5 days. It is important that the radiotherapy course not be protracted as choroidal metastases are usually part of the disseminated systemic disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, this treatment is only available at the specialized radiotherapy center and is quite costly. Furthermore, an unwanted side effect of central retinal vein occlusion has been reported six months after radiosurgery [8].…”
Section: Discussionmentioning
confidence: 99%
“…Advances in diagnostic tools and improved survival for breast cancer patients contribute to the increased occurrence of ocular metastasis. However, recent cases indicate improved treatment outcomes with the use of CDK4/6 inhibitors and stereotactic body radiotherapy (SBRT) [30]. External beam radiotherapy, with a typical dose ranging from 20 to 50 Gy, stabilizes or restores vision in up to 86% of patients [9,11,21,[31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Recently published cases [ 20 , 22 , 23 ] showed improvement in treatment outcomes secondary to the implementation of CDK4/6 inhibitors in combination with new RTH techniques like Stereotactic Body Radiotherapy (SBRT) [ 24 ]. Wiegel et al [ 26 ] showed that external beam radiotherapy (EBRTH) leads to stabilised or restored vision in up to 86% of patients; the typical dose varies between 20 and 50 Gy [ 3 , 5 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%